Creative health promotion methods for young LGBTIQA+ people. (October 2018) - Bellamy, Roz
This paper evaluates the potential efficacy of using life writing to address mental health disparities and to promote health and well-being among young LGBTIQA+ persons. It examines the potential benefits of young LGBTIQA+ people engaging with life writing including memoir, autobiography, creative nonfiction, journaling and digital storytelling. These benefits include exploring identity and making sense of one's experiences, unifying and empowering marginalised communities, providing people with agency, illuminating common experiences, and facilitating the exchange of resources and support. It evaluates current developments in literacy and English education and identifies an increasing trend towards neo-liberalism and economic discourses, potentially at the expense of providing opportunities for young people to develop creativity and engage in self-exploration. It discusses the author's experiences in running life writing workshops with groups of LGBTIQA+ young people and offers suggestions on how to run similar workshops in educational and wider community settings, including possible prompts, modes of working and debriefing the participants. Overall, the findings suggest that life writing can be used to improve the health and well-being of LGBTIQA+ young people; however, the paper concludes that this sort of intervention needs to be run respectfully, strategically and with full awareness of how sensitive and traumatic the content may be that can emerge for young people. For this reason, the paper presents guidelines and recommendations to provide structure and support.